Making a donation to church legal entities conducting service of charity activities to prevent, counteract and combat the effects of the Covid-19 epidemic - Poniatowski, Michał (Prawo Kanoniczne, 2020)
The article presents the issue of donating to ecclesiastical legal persons engaged in service of charity for the prevention, counteraction and combating the effects of the COVID-19 epidemic. The starting point was to present the general basis for donating. Subsequently, the personal and content aspect of donations made for the fight against COVID-19 was presented. In this respect, the changes introduced during the epidemic were emphasized. In the article also presents practical comments on the donation agreement. The most important conclusions were presented in the conclusion.